On the Periods of 2-Step General Fibonacci Sequences in the Generalized Quaternion Groups - Bahram Ahmadi; Hossein Doostie (Discrete Dynamics in Nature and Society)
We study 2-step general Fibonacci sequences in the generalized quaternion groups Q4n. In cases where the sequences are proved to be simply periodic, we obtain the periods of 2-step general Fibonacci sequences.